A method of electrochemical synthesis of ammonia
Patent Information
- Application Number
- CN202111520461.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-13
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2041-12-13
AI Technical Summary
但是利用化学链进行电化学合成氨还鲜有报道,具有很大的研究前景
[0047] 1. The efficient chemical chain electrochemical ammonia synthesis system provided in this application utilizes the excellent electrochemical nitrogen fixation performance of alkaline earth metal hydrides (such as LiH) and the excellent electrochemical hydrogenation ammonia production performance of the imino compounds (such as Li2NH) generated after nitrogen fixation to achieve an efficient chemical chain electrochemical ammonia synthesis process.
Abstract
Description
Technical Field
[0001] This application belongs to the field of electrochemical ammonia synthesis, and specifically relates to a method for electrochemical ammonia synthesis. Background Technology
[0002] Ammonia is a fundamental raw material for the production of important chemical products such as fertilizers, nitric acid, plastics, and pharmaceuticals. It is also a hydrogen source carrier with potential applications, making its synthesis and decomposition industrially significant. Catalytic conversion of nitrogen and hydrogen over transition metals is the main method for industrial ammonia synthesis, currently primarily using the Haber-Bosch process. This process requires harsh reaction conditions (iron-based catalysts: 350-525℃, 100-300 atm), demanding high-performance equipment and resulting in high energy consumption, accounting for 1% of the world's annual energy consumption. Currently, iron-based and ruthenium-based catalysts are still widely used in industrial ammonia synthesis; however, the efficiency of ammonia synthesis has not significantly improved over the decades, and high-temperature, high-pressure reaction conditions are still required. Therefore, developing a highly efficient ammonia synthesis process under mild conditions remains a crucial research topic.
[0003] Compared with the traditional Haber-Bosch process, electrochemical synthesis technology has many advantages, such as the ability to obtain electricity from renewable resources such as wind, solar and tidal energy, green sustainability, moderate reaction conditions, and the ability to be carried out at room temperature and pressure. It also has low equipment costs for ammonia synthesis, can use water instead of fossil fuels to provide hydrogen during the synthesis process, and has abundant raw materials. As a result, it has attracted widespread attention from researchers in recent years.
[0004] Chemical looping is an emerging research field that has shown advantages in areas such as fossil fuel combustion, syngas production, and hydrogen generation. In recent years, the chemical looping process for ammonia synthesis has attracted increasing attention due to its ease of coupling with renewable energy sources, atmospheric pressure operation, and avoidance of reactant adsorption competition. However, reports on the electrochemical synthesis of ammonia using chemical looping are still scarce, indicating significant research potential.
[0005] In current chloride molten salt systems, the ammonia production rate is extremely low. Although some studies have reported that adding Li3N can improve the ammonia production rate, the stability is very poor and the material lifespan is very short. These problems restrict the further development of electrochemical ammonia synthesis from chloride molten salts. Summary of the Invention
[0006] To overcome the aforementioned problems, as well as one or more other defects, disadvantages, and challenges, of existing molten salt electrochemical ammonia synthesis methods, this application provides a novel molten salt electrochemical ammonia synthesis process utilizing a chemical chaining process, exhibiting excellent ammonia production rate and stability. While this application will be described in conjunction with certain embodiments, it is not limited to these embodiments. Rather, this application includes all alternatives, modifications, and equivalents within the scope of this application.
[0007] According to one aspect of this application, a method for electrochemically synthesizing ammonia includes at least the following steps:
[0008] Nitrogen gas is introduced into an electrolytic cell containing electrolyte and electrodes to cause a nitrogen fixation reaction, and then hydrogen gas is introduced to cause a hydrogenation reaction to produce NH3.
[0009] The electrolyte includes an electrolyte, a nitrogen carrier, and a proton source;
[0010] The electrolyte is selected from chlorides or hydroxides in the molten state;
[0011] Optionally, the chloride in the molten state is selected from at least one of LiCl, NaCl, or KCl in the molten state;
[0012] Optionally, the molten chloride contains 50% LiCl molar amount and the molar ratio of NaCl to KCl is 0.2 to 0.8.
[0013] When the electrolyte is a chloride in a molten state, it is prepared by the following process: drying LiCl, NaCl and KCl at 200-500℃ for 5 hours, cooling and then transferring them to a glove box for storage.
[0014] Optionally, the hydroxide in the molten state is selected from at least one of LiOH, NaOH, or KOH in the molten state;
[0015] Optionally, the molar ratio of NaOH to KOH in the molten hydroxide is 0.2 to 0.8.
[0016] When the electrolyte is a hydroxide in a molten state, it is prepared by the following process: drying LiOH, NaOH, and KOH at 200–500°C for 5 hours, cooling, and then transferring them to a glove box for storage.
[0017] The nitrogen carrier is selected from lithium hydride or alkaline earth metal hydride.
[0018] Optionally, the alkaline earth metal hydride is selected from at least one of BaH2, CaH2, or MgH2;
[0019] The mass ratio of the nitrogen carrier to the electrolyte is 0.01 to 0.5.
[0020] The nitrogen carrier and electrolyte are mixed by ball milling or grinding.
[0021] The proton source is selected from water and ethanol;
[0022] The mass ratio of the proton source to the nitrogen carrier is 0.01 to 0.1;
[0023] Optionally, the proton source is selected from hydrogen gas;
[0024] The flow rate of the hydrogen gas is 10–100 mL / min.
[0025] The electrode includes an anode and a cathode;
[0026] The anode is selected from metal sheets or nickel foam;
[0027] Optionally, the metal sheet is selected from nickel, iron, or copper sheets;
[0028] The cathode is selected from nickel foam.
[0029] The electrode measures 1.0cm x 0.9cm.
[0030] The pressure for the nitrogen fixation reaction and the hydrogenation reaction is 1 atmosphere.
[0031] The flow rate of nitrogen gas in the nitrogen fixation reaction is 10–100 mL / min;
[0032] The nitrogen fixation reaction takes 0.5 to 2 hours;
[0033] Optionally, the nitrogen fixation reaction takes 1 to 2 hours;
[0034] The voltage for the nitrogen fixation reaction is 0.5–2.5V.
[0035] In the hydrogenation reaction, the flow rate of hydrogen is 10–100 mL / min;
[0036] The hydrogenation reaction takes 0.5 to 3 hours;
[0037] Optionally, the hydrogenation reaction takes 1 to 3 hours;
[0038] The voltage for the hydrogenation reaction is 0.2–2.25 V.
[0039] The nitrogen carrier is obtained by nitrogen fixation reaction to form a nitrogen-containing nitrogen carrier; the nitrogen-containing nitrogen carrier is obtained by hydrogenation reaction to form NH3 and a nitrogen carrier.
[0040] The specific process is as follows:
[0041] At the beginning of each cycle, i.e. before the nitrogen fixation process begins, high-purity nitrogen gas is introduced into the electrolytic cell.
[0042] During the nitrogen fixation process, high-purity nitrogen gas is introduced simultaneously with the application of electricity, and the nitrogen carrier will be nitrided to generate an imino compound.
[0043] After the nitrogen fixation process is completed, the nitrogen gas is switched to hydrogen gas in place through the six-way valve, and the working voltage is adjusted to the hydrogen addition voltage at the same time.
[0044] During the hydrogenation process, high-purity hydrogen gas is introduced into the electrolytic cell. The imino compounds produced during the nitrogen fixation process will react with protons under the action of voltage to generate NH3, and regenerate the nitrogen carrier, thus realizing the entire chemical cycle.
[0045] The generation rate of NH3 is not less than 1500 μmol / g / h.
[0046] Compared with the prior art, this application has the following advantages and beneficial effects:
[0047] 1. The efficient chemical chain electrochemical ammonia synthesis system provided in this application utilizes the excellent electrochemical nitrogen fixation performance of alkaline earth metal hydrides (such as LiH) and the excellent electrochemical hydrogenation ammonia production performance of the imino compounds (such as Li2NH) generated after nitrogen fixation to achieve an efficient chemical chain electrochemical ammonia synthesis process.
[0048] 2. The efficient chemical chain electrochemical ammonia synthesis system provided in this application uses MH2 and MNH as nitrogen carriers to realize the chemical chain cycle dominated by MH2→MNH→MH2 (M=LiNa Mg Ca Ba), providing a novel electrochemical ammonia synthesis pathway with broad research and application prospects. Detailed Implementation
[0049] The following examples further illustrate the specific implementation of this application, but the implementation and protection of this application are not limited thereto. It should be noted that any details not specifically described below are for reference by those skilled in the art for implementation or understanding. Reagents and instruments used without a specified manufacturer are considered to be conventional products available on the market.
[0050] Example 1:
[0051] Step 1: In an argon glove box, accurately weigh 0.0100g of lithium hydride (LiH) and 0.9900g of dried mixed chlorides (NaCl, KCl, LiCl). The masses of the three chlorides are 0.1980g, 0.3960g, and 0.3960g, respectively. Grind and mix them thoroughly and place them in an alumina crucible. Place the crucible in a self-made quartz electrolytic cell, using nickel foam as the electrode. The electrode size is 1cm × 0.9cm. Seal the electrolytic cell.
[0052] Step 2: Introduce argon gas into the electrolytic cell and heat it to 400°C to fully melt the electrolyte.
[0053] Step 3: Introduce high-purity nitrogen gas into the electrolytic cell at a flow rate of 30 ml / min, turn on the power supply, and react for 1 hour at a working voltage of 1.5V.
[0054] Step 4: In situ, switch nitrogen to high-purity hydrogen at a flow rate of 15 ml / min and react for 2 hours at a working voltage of 1.5V.
[0055] Step 5: Pass the exhaust gas into an exhaust gas absorber containing 100ml of dilute sulfuric acid solution, and use a conductivity meter to detect the amount of ammonia generated.
[0056] Step Six: Collect the dilute sulfuric acid solution after the tail gas. Use a salicylic acid spectrophotometer to determine the ammonia content in the absorber at 655 nm using a UV spectrophotometer, and compare the result with the conductivity meter method. The results show that the ammonia production rate is 1643 μmol / g / h, and the Faraday efficiency is 7.5%.
[0057] Example 2:
[0058] Step 1: In an argon glove box, accurately weigh 0.0100g of lithium hydride (LiH) and 0.9900g of dried mixed chlorides (NaCl, KCl, LiCl). The masses of the three chlorides are 0.1980g, 0.3960g, and 0.3960g, respectively. Grind and mix them thoroughly and place them in an alumina crucible. Place the crucible in a self-made quartz electrolytic cell, using nickel foam as the electrode. The electrode size is 1cm × 0.9cm. Seal the electrolytic cell.
[0059] Step 2: Introduce argon gas into the electrolytic cell and heat it to 400°C to fully melt the electrolyte.
[0060] Step 3: Introduce high-purity nitrogen gas into the electrolytic cell at a flow rate of 30 ml / min, turn on the power supply, and react for 1 hour at a working voltage of 1.5V.
[0061] Step 4: In situ, switch nitrogen to high-purity hydrogen at a flow rate of 15 ml / min and react for 2 hours at a working voltage of 1.75 V.
[0062] Step 5: Pass the exhaust gas into an exhaust gas absorber containing 100ml of dilute sulfuric acid solution, and use a conductivity meter to detect the amount of ammonia generated.
[0063] Step Six: Collect the dilute sulfuric acid solution after the tail gas. Use a salicylic acid spectrophotometer to determine the ammonia content in the absorber at 655 nm using a UV spectrophotometer, and compare the result with the conductivity meter method. The results show that the ammonia production rate is 1947 μmol / g / h, and the Faraday efficiency is 8.4%.
[0064] Example 3:
[0065] Step 1: In an argon glove box, accurately weigh 0.0100g of lithium hydride (LiH) and 0.9900g of dried mixed chlorides (NaCl, KCl, LiCl). The masses of the three chlorides are 0.1980g, 0.3960g, and 0.3960g, respectively. Grind and mix them thoroughly and place them in an alumina crucible. Place the crucible in a self-made quartz electrolytic cell, using nickel foam as the electrode. The electrode size is 1cm × 0.9cm. Seal the electrolytic cell.
[0066] Step 2: Introduce argon gas into the electrolytic cell and heat it to 400°C to fully melt the electrolyte.
[0067] Step 3: Introduce high-purity nitrogen gas into the electrolytic cell at a flow rate of 30 ml / min, turn on the power supply, and react for 1 hour at a working voltage of 1.5V.
[0068] Step 4: In situ, switch nitrogen to high-purity hydrogen at a flow rate of 15 ml / min and react for 2 hours at a working voltage of 2.0 V.
[0069] Step 5: Pass the exhaust gas into an exhaust gas absorber containing 100ml of dilute sulfuric acid solution, and use a conductivity meter to detect the amount of ammonia generated.
[0070] Step Six: Collect the dilute sulfuric acid solution after the tail gas. Use a salicylic acid spectrophotometer to determine the ammonia content in the absorber at 655 nm using a UV spectrophotometer, and compare the result with the conductivity meter method. The results show that the ammonia production rate is 2872 μmol / g / h, and the Faraday efficiency is 11.7%.
[0071] Example 4:
[0072] Step 1: In an argon glove box, accurately weigh 0.0100g of lithium hydride (LiH) and 0.9900g of dried mixed chlorides (NaCl, KCl, LiCl). The masses of the three chlorides are 0.1980g, 0.3960g, and 0.3960g, respectively. Grind and mix them thoroughly and place them in an alumina crucible. Place the crucible in a self-made quartz electrolytic cell, using nickel foam as the electrode. The electrode size is 1cm × 0.9cm. Seal the electrolytic cell.
[0073] Step 2: Introduce argon gas into the electrolytic cell and heat it to 400°C to fully melt the electrolyte.
[0074] Step 3: Introduce high-purity nitrogen gas into the electrolytic cell at a flow rate of 30 ml / min, turn on the power supply, and react for 1 hour at a working voltage of 1.75V.
[0075] Step 4: In situ, switch nitrogen to high-purity hydrogen at a flow rate of 15 ml / min and react for 2 hours at a working voltage of 1.5V.
[0076] Step 5: Pass the exhaust gas into an exhaust gas absorber containing 100ml of dilute sulfuric acid solution, and use a conductivity meter to detect the amount of ammonia generated.
[0077] Step Six: Collect the dilute sulfuric acid solution after the tail gas. Use a salicylic acid spectrophotometer to determine the ammonia content in the absorber at 655 nm using a UV spectrophotometer, and compare the result with the conductivity meter method. The results show that the ammonia production rate is 1967 μmol / g / h, and the Faraday efficiency is 8.1%.
[0078] Example 5:
[0079] Step 1: In an argon glove box, accurately weigh 0.0100g of lithium hydride (LiH) and 0.9900g of dried mixed chlorides (NaCl, KCl, LiCl). The masses of the three chlorides are 0.1980g, 0.3960g, and 0.3960g, respectively. Grind and mix them thoroughly and place them in an alumina crucible. Place the crucible in a self-made quartz electrolytic cell, using nickel foam as the electrode. The electrode size is 1cm × 0.9cm. Seal the electrolytic cell.
[0080] Step 2: Introduce argon gas into the electrolytic cell and heat it to 400°C to fully melt the electrolyte.
[0081] Step 3: Introduce high-purity nitrogen gas into the electrolytic cell at a flow rate of 30 ml / min, turn on the power supply, and react for 1 hour at a working voltage of 1.75V.
[0082] Step 4: In situ, switch nitrogen to high-purity hydrogen at a flow rate of 15 ml / min and react for 2 hours at a working voltage of 1.75 V.
[0083] Step 5: Pass the exhaust gas into an exhaust gas absorber containing 100ml of dilute sulfuric acid solution, and use a conductivity meter to detect the amount of ammonia generated.
[0084] Step Six: Collect the dilute sulfuric acid solution after the tail gas. Use a salicylic acid spectrophotometer to determine the ammonia content in the absorber at 655 nm using a UV spectrophotometer, and compare the result with the conductivity meter method. The results show that the ammonia production rate is 2436 μmol / g / h, and the Faraday efficiency is 9.7%.
[0085] Example 6:
[0086] Step 1: In an argon glove box, accurately weigh 0.0100g of lithium hydride (LiH) and 0.9900g of dried mixed chlorides (NaCl, KCl, LiCl). The masses of the three chlorides are 0.1980g, 0.3960g, and 0.3960g, respectively. Grind and mix them thoroughly and place them in an alumina crucible. Place the crucible in a self-made quartz electrolytic cell, using nickel foam as the electrode. The electrode size is 1cm × 0.9cm. Seal the electrolytic cell.
[0087] Step 2: Introduce argon gas into the electrolytic cell and heat it to 400°C to fully melt the electrolyte.
[0088] Step 3: Introduce high-purity nitrogen gas into the electrolytic cell at a flow rate of 30 ml / min, turn on the power supply, and react for 1 hour at a working voltage of 1.75V.
[0089] Step 4: In situ, switch nitrogen to high-purity hydrogen at a flow rate of 15 ml / min and react for 2 hours at a working voltage of 2.0 V.
[0090] Step 5: Pass the exhaust gas into an exhaust gas absorber containing 100ml of dilute sulfuric acid solution, and use a conductivity meter to detect the amount of ammonia generated.
[0091] Step Six: Collect the dilute sulfuric acid solution after the tail gas. Use a salicylic acid spectrophotometer to determine the ammonia content in the absorber at 655 nm using a UV spectrophotometer, and compare the result with the conductivity meter method. The results show that the ammonia production rate is 3847 μmol / g / h, and the Faraday efficiency is 13.1%.
[0092] Example 7:
[0093] Step 1: In an argon glove box, accurately weigh 0.0100g of lithium hydride (BaH2) and 0.9900g of dried mixed hydroxides (NaOH, KOH). The mass of each hydroxide is 0.495g. Grind and mix them thoroughly, place them in an alumina crucible, and put them in a self-made quartz electrolytic cell. Use nickel foam as the electrode, with an electrode size of 1cm × 0.9cm. Seal the electrolytic cell.
[0094] Step 2: Introduce argon gas into the electrolytic cell and heat it to 260°C to fully melt the electrolyte.
[0095] Step 3: Introduce high-purity nitrogen gas into the electrolytic cell at a flow rate of 30 ml / min, turn on the power supply, and react for 1 hour at a working voltage of 1.75V.
[0096] Step 4: In situ, switch nitrogen to high-purity hydrogen at a flow rate of 15 ml / min and react for 2 hours at a working voltage of 1.50 V.
[0097] Step 5: Pass the exhaust gas into an exhaust gas absorber containing 100ml of dilute sulfuric acid solution, and use a conductivity meter to detect the amount of ammonia generated.
[0098] Step Six: Collect the dilute sulfuric acid solution after the tail gas. Use a salicylic acid spectrophotometer to determine the ammonia content in the absorber at 655 nm using a UV spectrophotometer, and compare the result with the conductivity meter method. The results show that the ammonia production rate is 2637 μmol / g / h, and the Faraday efficiency is 12.7%.
[0099] Example 8:
[0100] Step 1: In an argon glove box, accurately weigh 0.0100g of lithium hydride (BaH2) and 0.9900g of dried mixed hydroxides (NaOH, KOH). The mass of each hydroxide is 0.495g. Grind and mix them thoroughly, place them in an alumina crucible, and put them in a self-made quartz electrolytic cell. Use nickel foam as the electrode, with an electrode size of 1cm × 0.9cm. Seal the electrolytic cell.
[0101] Step 2: Introduce argon gas into the electrolytic cell and heat it to 260°C to fully melt the electrolyte.
[0102] Step 3: Introduce high-purity nitrogen gas into the electrolytic cell at a flow rate of 30 ml / min, turn on the power supply, and react for 1 hour at a working voltage of 1.75V.
[0103] Step 4: In situ, switch nitrogen to high-purity hydrogen at a flow rate of 15 ml / min and react for 2 hours at a working voltage of 1.75 V.
[0104] Step 5: Pass the exhaust gas into an exhaust gas absorber containing 100ml of dilute sulfuric acid solution, and use a conductivity meter to detect the amount of ammonia generated.
[0105] Step Six: Collect the dilute sulfuric acid solution after the tail gas. Use a salicylic acid spectrophotometer to determine the ammonia content in the absorber at 655 nm using a UV spectrophotometer, and compare the result with the conductivity meter method. The results show that the ammonia production rate is 3461 μmol / g / h, and the Faraday efficiency is 14.6%.
[0106] Example 9:
[0107] Step 1: In an argon glove box, accurately weigh 0.0100g of lithium hydride (BaH2) and 0.9900g of dried mixed hydroxides (NaOH, KOH). The mass of each hydroxide is 0.495g. Grind and mix them thoroughly, place them in an alumina crucible, and put them in a self-made quartz electrolytic cell. Use nickel foam as the electrode, with an electrode size of 1cm × 0.9cm. Seal the electrolytic cell.
[0108] Step 2: Introduce argon gas into the electrolytic cell and heat it to 260°C to fully melt the electrolyte.
[0109] Step 3: Introduce high-purity nitrogen gas into the electrolytic cell at a flow rate of 30 ml / min, turn on the power supply, and react for 1 hour at a working voltage of 1.75V.
[0110] Step 4: In situ, switch nitrogen to high-purity hydrogen at a flow rate of 15 ml / min and react for 2 hours at a working voltage of 1.75 V.
[0111] Step 5: Pass the exhaust gas into an exhaust gas absorber containing 100ml of dilute sulfuric acid solution, and use a conductivity meter to detect the amount of ammonia generated.
[0112] Step Six: Collect the dilute sulfuric acid solution after the tail gas. Use a salicylic acid spectrophotometer to determine the ammonia content in the absorber at 655 nm using a UV spectrophotometer, and compare the result with the conductivity meter method. The results show that the ammonia production rate is 5137 μmol / g / h, and the Faraday efficiency is 19.3%.
[0113] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for electrochemical synthesis of ammonia, characterized in that, At least the following steps are included: Nitrogen gas is introduced into an electrolytic cell containing an electrolyte and a nitrogen carrier, and the nitrogen carrier undergoes a nitrogen fixation reaction with the nitrogen gas to obtain a nitrogen-containing nitrogen carrier; A proton source is added to the electrolytic cell, and the nitrogen-containing nitrogen carrier undergoes a hydrogenation reaction with the proton source to obtain NH3; The electrolyte is selected from at least one of the chlorides or hydroxides of Li, Na, or K in the molten state; The nitrogen carrier is selected from lithium hydride or alkaline earth metal hydride. The electrolytic cell includes electrodes, and the electrodes include an anode and a cathode; The anode is selected from metal sheets or nickel foam; The metal sheet is selected from nickel sheet, iron sheet or copper sheet; The cathode is selected from nickel foam.
2. The method according to claim 1, characterized in that, The chlorides of Li, Na, or K in the molten state are selected from at least one of LiCl, NaCl, or KCl in the molten state.
3. The method according to claim 1, characterized in that, The chlorides of Li, Na, or K in the molten state are selected from at least two of LiCl, NaCl, or KCl in the molten state.
4. The method according to claim 3, characterized in that, In the molten state, the Li chloride contains 50% LiCl molar content, and the molar ratio of NaCl to KCl is 0.2~0.
8.
5. The method according to claim 1, characterized in that, The molten Li, Na, or K hydroxide is selected from at least one of LiOH, NaOH, or KOH in the molten state.
6. The method according to claim 1, characterized in that, The molten Li, Na, or K hydroxide is selected from at least two of LiOH, NaOH, or KOH in the molten state.
7. The method according to claim 6, characterized in that, The molten Li hydroxide contains 50% LiOH molar amount, and the Na, or K hydroxide contains NaOH and KOH molar ratios of 0.2 to 0.
8.
8. The method according to claim 1, characterized in that, The mass ratio of the nitrogen carrier to the electrolyte is 0.01 to 0.5; The alkaline earth metal hydride is selected from at least one of BaH2, CaH2, or MgH2.
9. The method according to claim 1, characterized in that, The proton source is selected from water, hydrogen, or ethanol; The mass ratio of the proton source to the nitrogen carrier is 0.01 to 0.1; The flow rate of the hydrogen gas is 10~100 mL / min.
10. The method according to claim 1, characterized in that, The pressure for the nitrogen fixation reaction and the hydrogenation reaction is 1 atmosphere.
11. The method according to claim 1, characterized in that, The flow rate of nitrogen gas in the nitrogen fixation reaction is 10~100 mL / min; The nitrogen fixation reaction takes 0.5 to 2 hours.
12. The method according to claim 1, characterized in that, The nitrogen fixation reaction takes 1 to 2 hours; The voltage for the nitrogen fixation reaction is 0.5~2.5V.
13. The method according to claim 1, characterized in that, In the hydrogenation reaction, the flow rate of hydrogen is 10~100mL / min; The hydrogenation reaction takes 0.5 to 3 hours.
14. The method according to claim 1, characterized in that, The hydrogenation reaction takes 1 to 3 hours; The voltage for the hydrogenation reaction is 0.2~2.25V; When the nitrogen carrier is LiH, the nitrogen-containing nitrogen carrier is Li2NH.
15. The method according to claim 1, characterized in that, The generation rate of NH3 is not less than 1500 μmol / g / h.